Concentrated Electrolytes and Their Unique Interfacial Reactions in Rechargeable Batteries - Ryoichi TATARA (Electrochemistry)
An electrolyte is an important component of rechargeable batteries. The Debye–Hückel theory is applicable to liquid electrolytes with salt concentrations up to approximately 0.01 mol/L. Thus, electrolyte solutions with approximately 1 mol/L salt concentration are considered “highly concentrated” from the perspective of the classical solution theory. However, electrochemical devices use them at these concentrations, because their ionic conductivity reaches the maximum level across the entire concentration range. Although a salt concentration of 1 mol/L is considered very high, recent studies have indicated that the use of further “super-concentrated” electrolytes, typically those with concentrations exceeding 3 mol/L and also known as “molten solvate” or “solvent-in-salt” can exhibit unique reaction behaviors in various electrochemical systems, including Li-ion batteries. This review examines the characteristics of such “super-concentrated” electrolytes.